Pengembangan Multimedia Interaktif Informasi Karier untuk Meningkatkan Kematangan Karier Siswa Sekolah Menengah Kejuruan - Risqiyain, Liya Husna; Purwanta, Edi (Jurnal Kajian Bimbingan dan Konseling, 2019)
Adolescence is a crucial phase of life where individuals need to choose a particular career. In choosing a career, many individuals experience problems. This study aims to: (1) create an interactive multimedia product containing career information to improve vocational high school students’ career maturity; (2) reveal the quality of interactive multimedia containing career information in improving vocational high school students’ career; and (3) understand the effectiveness of interactive multimedia containing career information in improving vocational high school students’ career maturity. This research development referred to Borg & Gall’s development research. In the feasibility stage, data collection was conducted by distributing multimedia feasibility test questionnaires to media experts and material experts; assessment questionnaires to students; and career maturity scale. Results indicated that the use of interactive multimedia containing career information effectively increased vocational high school students’ career maturity.